Розвиток теорії діелькометричної вологометрії та алгоритмічних методів підвищення точності вимірювання вмісту вологи речовин - Заболотний, Олександр Віталійович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Дисертація на здобуття наукового ступеня доктора технічних наук за спеціальністю 05.11.13 «Прилади і методи контролю та визначення складу речовин». – Національний аерокосмічний університет ім. М. Є. Жуковського «Харківський авіаційний інститут», Харків, 2019. Дисертацію присвячено проблемі підвищення точності вимірювання вмісту вологи різних матеріалів шляхом розроблення нових методів визначення вмісту вологи, а також розробки нових первинних і вторинних перетворювачів вмісту вологи. В дисертаційній роботі здійснено порівняльний аналіз відомих способів вимірювання вмісту вологи, що передбачають тестові впливи на речовину. Для більшості відомих тестових алгоритмів, використаних для визначення вмісту вологи, вплив «сортової невизначеності» на результат вимірювання є дуже суттєвим. Вперше здійснено теоретичну перевірку обумовленості значень вмісту вологи, отриманих в результаті застосування запропонованих тестових алгоритмів. Як наслідок було синтезовано новий метод визначення вмісту вологи, в якому тестовий алгоритм утворено з двох адитивних, двох мультиплікативних і одного додаткового тестів і використання якого дозволило забезпечити задовільний рівень обумовленості обчислених значень. Було здійснено порівняльний аналіз запропонованих тестових алгоритмів за допомогою двох мір відстані між обчисленими і номінальними значеннями вмісту вологи. Показано, що новий метод визначення вмісту вологи забезпечує найменшу розбіжність із номінальними значеннями вмісту вологи і є найбільш придатним для використання. Також було запропоновано диференційний метод вимірювання вмісту вологи сипких і рідинних матеріалів, що передбачає використання чотирьох вимірювальних конденсаторів, два з яких заповнюють пробою досліджуваної речовини, а інші два – пробою такої ж речовини, але попередньо зневодненої, який має меншу чутливість до зміни сорту речовини (∆̅ Σ = 0,72%) у порівнянні з класичною диференційною схемою (∆̅ Σ = 1,16%). Вперше отримано математичні моделі статичних характеристик перетворення для ємнісних первинних вимірювальних перетворювачів вмісту вологи, які дозволили провести порівняльний аналіз термокомпенсаційних властивостей одинарного первинного перетворювача, класичного диференційного та первинного перетворювача, сформованого з чотирьох вимірювальних конденсаторів. Після розроблення і виготовлення дослідних зразків первинних і вторинних вимірювальних перетворювачів, було проведено серію експериментів для визначення рівня впливу сорту речовини на результат вимірювання вмісту вологи з використанням диференційного методу і методу з тестовим алгоритмом, утвореним з двох адитивних, двох мультиплікативних і одного додаткового тестів. Результати експериментів показали низьку чутливість до зміни сорту речовини. Результати проведених теоретичних і експериментальних досліджень використані у практиці таких підприємств і організацій: ТОВ «ВО ОВЕН» (Харків, Україна); ПП «ЄС - Автоматика» (Харків, Україна); УА ТОВ ФІРМА «КОДА» (Харків, Україна); навчальний процес Національного аерокосмічного університету ім. М. Є. Жуковського «Харківський авіаційний інститут».

Dissertation for Doctor Degree of Technical Science (Doctor of Science) in specialty 05.11.13 “Devices and Methods of Control and Defining the Composition of Materials”. – National Aerospace University “Kharkiv Aviation Institute”, Kharkiv, 2019. The dissertation is dedicated to the problem of different materials moisture measurement accuracy increase in a way of new methods of moisture measurement development, synthesis of a new testing algorithms to calculate the quantity of moisture, conditionality examination for the solutions, received with a help of new testing algorithms, development of a new mathematical models of a static transformation characteristics, able to consider the influence of material’s type, temperature and granulometric composition of a material under research, and new initial and secondary transducers of moisture measurement development. In the dissertation we can find a comparative analysis of already developed methods of moisture measurement, provided for testing influences on the material under research. As a result, it was determined that for most of already developed testing algorithms used to calculate the result of moisture measurement the influence of “type uncertainty” is significant. To synthesize more adequate tests the function, which describes deviation of a simplified test from the universal Wiener equation, had been graphically defined with its approximation by the instruments of general type linear regression. The function of amendment had been received after approximation. Adding it to the simplified Wiener equation allowed to provide complete overlap of simplified and original Wiener formulas. The new testing algorithm, that should decrease variation between calculated and standard moisture values had been created. Really, decrease of variation had been provided, but invariance to the type of material disappeared. These attempt can not be called successful. After that a new principle of testing algorithms using least squares method and different Lagrange polynomials had been suggested. It allowed to wide the adequate range of moisture values up to 30 %, but maximal variation still has a value of 7,4 % and we don’t have effective “type uncertainty” compensation. Testing algorithm, synthesized from one additive and one multiplicative test, provided maximal deviation of 1,5 % from linear function in comparison with 3,6 % for the best analogue. To decrease variation between standard and calculated values of moisture new testing algorithm with one additive, one multiplicative and one complementary tests had been suggested. Maximal variation for it has a value of 1,16 % taking the full range of moisture measurement from 0 % to 40 %. For the first time it was done theoretical verification of the moisture values conditionality, obtained with a help of developed testing algorithms application. Mentioned above testing algorithms happened to be unusable because of low moisture values conditionality in a points 0 % and 10 % of moisture control. That’s why the new method of moisture measurement, where a testing algorithm had been constructed from two additive, two multiplicative and two complementary tests had been developed. It’s application allowed to provide conditionality of calculated moisture values at satisfactory level. A comparison analysis had been fulfilled for three best analogues and the last testing algorithm with a help of two measures of distance between calculated and nominal moisture values. It allowed to see that new method of moisture measurement provides the smallest deviation with standard moisture values and is preferable to use. During further researches a new differential method of moisture measurement for dry and liquid materials had been suggested. It provides the usage of four measuring capacitors, where two of them are filled with a probe of the material under research and the rest of capacitors should be filled with same material, but previously dehydrated. The method provides low sensitivity to the type of researched material (∆̅ Σ = 0,72%) in comparison with traditional differential method of measurement (∆̅ Σ = 1,16%). New mathematical models of a static transformation characteristics for the capacitance initial measuring transducers have been received for the first time, that allowed to fulfill the comparison analysis of thermal compensation properties for single initial transducer, classic differential transducer and a transducer, created from four measuring capacitors. After capacitance initial and secondary transducers had been developed, some number of experiments had been carried out to define the level of material’s type influence on the result of moisture measurement when using the new differential method and a method with testing algorithm, synthesized from two additive, two multiplicative and one complementary tests. Results of these experiments showed low sensitivity to the material’s type variation. Results of fulfilled theoretical and experimental researches are implemented in practice of such a firms and organizatios: limited company “VO OVEN” (Kharkiv, Ukraine); industrial enterprise “ES – Automatica” (Kharkiv, Ukraine); limited company “KODA” (Kharkiv, Ukraine); in the learning process of National Aerospace University (Kharkiv, Ukraine).
Theory of dielcometer moisture metering and algorithmic methods of accuracy increase development for different substances moisture metering
Keywords: автореферат дисертації; контроль вмісту вологи; діелектрична проникність; сортова невизначеність; тестовий алгоритм; тестові методи вимірювань; обумовленість; moisture control; dielectric permittivity; type uncertainty; testing algorithm; testing methods of measurement; conditionality; 621.317.39